2019
DOI: 10.1590/1678-4162-10390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dexamethasone and surfactant in the vitality and lung function of preterm lambs born by cesarean section

Abstract: The aim of this study was to assess the vitality and lung function of preterm lambs. Twenty seven preterm lambs were divided in four groups. Group I (n=6) preterm lambs/ control; group II (n=9) lambs born to mothers that were treated with dexamethasone antepartum; group III (n=6) lambs treated with surfactant; and group IV (n=6) lambs treated with surfactant and born to mothers that were treated with dexamethasone antepartum. The APGAR score was performed after birth (T0) and 15 minutes later (T1/4) to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This confirms that components such as serum, cholesterol, and triglycerides can directly inactivate the surfactant and induce changes in its dynamics [ 108 ]. For this reason, and supported by animal models in lambs and guinea pigs, it has been suggested that surfactant replacement therapy should be accompanied by a drug that allows its mechanism of action to be carried out successfully [ 109 , 110 ].…”
Section: Role Of the Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that components such as serum, cholesterol, and triglycerides can directly inactivate the surfactant and induce changes in its dynamics [ 108 ]. For this reason, and supported by animal models in lambs and guinea pigs, it has been suggested that surfactant replacement therapy should be accompanied by a drug that allows its mechanism of action to be carried out successfully [ 109 , 110 ].…”
Section: Role Of the Surfactantmentioning
confidence: 99%
“…The treatment of MAS is controversial; since its use does not clearly influence decreasing neonatal mortality incidence, monotherapies such as corticosteroids, antibiotics, and phosphodiesterase inhibitors have presented variable results over time in reducing clinical signs of MAS [ 7 , 17 , 114 ]. Thus, it might be necessary to explore the combined use or multimodal therapy of the different drugs, as has been observed with the combined use of surfactant with glucocorticoids or the use with antibiotics that can help reduce the inactivation of the surfactant by increasing resistance to it [ 109 , 115 ]. Likewise, explore the use of vasodilators not only to reduce the incidence of pulmonary hypertension but also to consider that they may avoid hypoxia and reduce acidosis in the newborn [ 116 , 117 ].…”
Section: Future Directionsmentioning
confidence: 99%